2005
DOI: 10.1002/cncr.21131
|View full text |Cite
|
Sign up to set email alerts
|

Metaanalysis of the significance of matrix metalloproteinases for lymph node disease in patients with head and neck squamous cell carcinoma

Abstract: Objective: To study the reliability of the sentinel node technique (SNT) in the management of the N0 neck in patients with supraglottic laryngeal cancer. Methods: Patients presenting to our department, between 2001 and 2004, with T1–T3 supraglottic cancer and N0 neck, clinically and radiologically, were included in the study. All patients underwent sentinel lymph node detection, using the hand‐held gamma probe followed by bilateral modified radical neck dissection (MRND) and resection of the primary tumor. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0
4

Year Published

2007
2007
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 20 publications
4
28
0
4
Order By: Relevance
“…This idea is further supported by data showing a reduced vascular density in chemically induced skin SCCs of MMP-3-deficient mice suggesting this protease as an important modulator of tumor vascularization and, thus, playing a potential role in this mechanism regulating tumor metastasis. 51,52 Taken together, our data show a clear dynamics of MMP expression associated with tumor progression and point out the complexity of MMP functions in vivo. Tumor cells migrating from the primary tumor border are interacting with the broad range of host-derived factors, most of which have evolved or are directed to defend the integrity of different host systems.…”
Section: Progression-associated Expression Of Mmp Mrna and Proteinmentioning
confidence: 73%
“…This idea is further supported by data showing a reduced vascular density in chemically induced skin SCCs of MMP-3-deficient mice suggesting this protease as an important modulator of tumor vascularization and, thus, playing a potential role in this mechanism regulating tumor metastasis. 51,52 Taken together, our data show a clear dynamics of MMP expression associated with tumor progression and point out the complexity of MMP functions in vivo. Tumor cells migrating from the primary tumor border are interacting with the broad range of host-derived factors, most of which have evolved or are directed to defend the integrity of different host systems.…”
Section: Progression-associated Expression Of Mmp Mrna and Proteinmentioning
confidence: 73%
“…On the contrary, Görögh et al [4] and O-Charoenrat et al [14] reported positive correlation between MMP-2 expression and nodal involvement, as has Xie et al [15] although specifically for Supraglottic laryngeal carcinoma. Regarding the different results reported, the metaanalysis on MMP expression and [16] should be taken into account which is supportive of the role of MMP-2 in tumor invasiveness, although stating a variety of shortcomings of the respective literature. Although MMP-2 expression was not related to nodal involvement, statistical significance was reached in our study for ruptured lymph node capsule in the small subgroup of patients who underwent neck dissection.…”
Section: Discussionmentioning
confidence: 95%
“…Standardization of staining procedures and evaluation protocols does help to compare the variability of published data and extract valid results. 126 Nevertheless, the existence of a considerable number of conflicting studies should be acknowledged, as well as the possibility that some studies indicating negative MMP expression in tumors are unlikely to be published. 50 In spite of these limitations, results of several studies evaluating MMP expression in HNSCCs provide insight into their prognostic importance.…”
Section: Mmps As Tumor Biomarkersmentioning
confidence: 99%